Capacitaciones tributarias del servicio de rentas internas agencia Quevedo y su incidencia en la recaudación del impuesto a las tierras rurales. Período 2013-2014 - Albán Moyano, Miryan Noemí (2015)
The Internal Revenue Service has as its purpose the collection of taxes throughout the country, this institution has agencies in several cantons of our territory to meet the objective of the institution, in the area of Quevedo considered purely agricultural the SRI account with a good amount of taxpayers who do not possess the necessary information for the performance of their tax obligations. This research was conducted with the purpose of evaluating the incidence of process skills in the collection of the tax to the rural lands in the agency of the Internal Revenue Service Quevedo. In the research work was interviewed the head of agency of SRI Quevedo. It is consulted in sources such as: brochures, writings, books, policies and regulations concerning the tax to the rural lands, laws and the Internet, and took into account statistical data that allow to visualize the evolution of the collection in selected periods in the present work. The amounts collected in the area of influence of the SRI Quevedo in 2013 was $ 202,437.28 and in 2014 was $ 271,642.91 while deriving from the whole province was $ 292,150.00 467,608.01 and respectively, which allows you to recommend parallel strategies according to the needs of those involved as the taxpayer and the SRI Quevedo.